Visual Expression of The Ancient Sundanese Manuscript Bujangga Manik into Batik Motifs - Tessa Eka Darmayanti1; Ratnadewi; Pandanwangi, Ariesa (Proceeding of International Conference on Art, Media, and Culture (ICAMAC), 2024)
Many people in the world travel to beautiful places by road, air or sea. But not all of these journeys are immortalised in a complete diary, which is why Bujangga Manik, a Sundanese rishi, was so special when his travel notes were so complete and written on palm leaves. The aim of the research is to visually reveal one of Bujangga Manik's journeys. The method used is descriptive qualitative method with a visual language approach. The sample of this research is a batik motif created based on the idea of Bujangga Manik's journey. The result of this research are batik motifs that were initiated from Bujangga Manik's journey that highlight local wisdom with red, yellow and black colours. The composition of batik motifs, arranged from the main motif that is made large and considered important, as a symbol of the object of importance. The batik motifs produced can become unique commercial products, able to attract the interest of the wider community and have economic potential, as well as opening up new market opportunities thereby increasing added value for the batik industry. These findings not only enrich batik designs, but also contribute to raising the local cultural and historical values contained in the Bujangga Manik manuscript. This research shows how ancient visual elements can be adapted and integrated into batik artwork, thus becoming a bridge between the past and the present.